2023
DOI: 10.5946/ce.2022.072
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of endoscopy under general anesthesia for the detection of synchronous lesions in oro-hypopharyngeal cancer

Abstract: Background/Aims: Image-enhanced endoscopy can detect superficial oro-hypopharyngeal squamous cell carcinoma; however, reliable endoscopy of the pharyngeal region is challenging. Endoscopy under general anesthesia during transoral surgery occasionally reveals multiple synchronous lesions that remained undetected on preoperative endoscopy. Therefore, we aimed to determine the lesion detection capability of endoscopy under general anesthesia for superficial oro-hypopharyngeal squamous cell carcinoma. Methods: Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Therefore, detailed observation of the oro-hypopharyngeal area during routine screening endoscopy is necessary. As demonstrated by Ono et al, 13 endoscopy under GA, along with panendoscopy, is helpful when selectively performed in patients stratified as having a high risk for recurrence.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Therefore, detailed observation of the oro-hypopharyngeal area during routine screening endoscopy is necessary. As demonstrated by Ono et al, 13 endoscopy under GA, along with panendoscopy, is helpful when selectively performed in patients stratified as having a high risk for recurrence.…”
mentioning
confidence: 96%
“…Ono et al 13 reported the capability of endoscopy under general anesthesia (GA), compared with that of conventional sedated endoscopy, for detecting superficial oro-hypopharyngeal SCC lesions. The mean number of lesions detected per patient was significantly higher on endoscopies performed under GA than on endoscopies performed under conventional sedation (1.47 vs. 1.17, p <0.001).…”
mentioning
confidence: 99%
“…They showed that newly detected lesions were small and characterized by few changes, color, and surface ruggedness. 1 These findings are important but not surprising, considering that transoral endoscopy with topical anesthesia can be uncomfortable. Even with conscious sedation, it can easily induce the gag reflex and make subsequent examination difficult.…”
mentioning
confidence: 97%
“…To the Editor, I read with interest the article by Ono et al 1 and the corresponding editorial by Noh and Kim 2 published in the recent issue of Clinical Endoscopy. Ono et al 1 studied patients with hypopharyngeal squamous cell carcinoma scheduled for transoral resection under general anesthesia and found more lesions (1.47 lesions/patient) during detailed assessment just before resection compared to previous transoral endoscopy (1.17 lesions/patient) done with or without sedation. They showed that newly detected lesions were small and characterized by few changes, color, and surface ruggedness.…”
mentioning
confidence: 99%